ANALISIS TINDAK PIDANA PENGGUNAAN ALAT RAPID TEST ANTIGEN BEKAS OLEH OKNUM PETUGAS MEDIS KIMIA FARMA - Indah Wahyuni Dian Ratnasari (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
The RT-PCR Test or rapid antigen test is a very profitable business for health service providers. This opportunity made the medical officer of Kimia Farma at Kualanamu International Airport Medan, North Sumatra took advantage of this situation by recycling the rapid antigen test kit. Therefore, it is necessary to study these problems with the formulation of problems that related to legal regulations that have been violated in the use of used rapid antigen test kit, as well as criminal threats that can be applied to the use of used rapid antigen test kit by the medical officer of Kimia Farma. The results of the study indicate that the actions of the medical officer of Kimia Farma are unlawful acts that violate various articles in the Health Law and the Consumer Protection Law. As well as the threat of criminal articles that can be applied to the medical officer is Article 196 of the Health Law (UU Kesehatan), Article 62 paragraph (1) of the Consumer Protection Law (UUPK), and Article 63 letter a of the Consumer Protection Law (UUPK).